Answer:
C=627.2
Step-by-step explanation:
Basically, joint variation is y=kxz. With the provided information, the equation you wanna use is C=k(a)^3(b)^2
Therefore, plug in C for Y, leave K as a variable, and plug in the numbers provided for a and b.
You get 25.6=k(2)^3(4)^2 . When simplified, you get 25.6=128k.
You then divide the 25.6 by the 128 to get .2=k
Now leave C as the variable and plug in the numbers. DON'T FORGET TO CUBE AND SQUARE THE NUMBERS.
It should look like C=(.2)(4)^3(7)^2 , or C=.2(64)(49)
C=627.2 .
Hope this helps, my mistake was forgetting to use the exponents. :)